Analisis Fundamental Mikro dan Struktur Kepemilikan Terhadap Kinerja Keuangan dengan Struktur Modal, Manajemen Laba, Karateristik Perusahaan sebagai Variabel Intervening pada Perusahaan Perbankan - Atakelan, Reinatto Yakobus Pati Agon; Hwihanus (LANCAH: Jurnal Inovasi dan Tren, 2024)
The purpose of the research activity is to determine and analyze the financial performance of banking companies on the Indonesia Stock Exchange from 2013 and 2018. A quantitative descriptive approach is used as a research method for secondary data, respectively for each independent and dependent variable. Where the independent variables are: Micro fundamentals, Ownership Structure, Capital Structure, Profit Management, Company Characteristics, and the dependent variable is: Financial Performance. Data is taken from financial reports and also the IDX website (www.idx.co.id). Banking companies on the IDX were involved in this research from 2013 to 2018. A sample of 5 banking companies was taken for analysis, using random sampling. From the results of the analysis, there is only one independent variable that has a significant effect on the dependent variable, and the remaining independent variables do not have a significant effect on financial performance.